THE EFFECT OF WORKING HOURS, BUSINESS CAPITAL, AND THE USE OF QRIS TECHNOLOGY ON TRADERS' INCOME AT PASAR AGUNG PENINJOAN - Ida Ayu Made Intan Dwicahyani; Luh Gede Meydianawathi (Adisam Publisher, 2025)
This study aims to analyze the effect of working hours, business capital, and the use of QRIS technology on the income of traders at Pasar Agung Peninjoan, Denpasar. The background of this research is based on the importance of the informal sector, particularly traditional markets, in supporting the community's economy, as well as the challenges faced by traders in adapting to competition and the development of digital technology. A quantitative approach was used with multiple linear regression analysis, based on data collected from 108 respondents. The findings show that both simultaneously and partially, working hours, business capital, and QRIS usage have a positive and significant effect on traders' income. These results indicate that income can be increased through optimizing working hours, capital support, and the use of digital payment technologies.